Estrategias lúdicas para la construcción de aprendizajes significativos en Química. Período lectivo 2022 –2023 - Alvarado González, Ana Mercedes (2023)
The implementation of ludic didactic strategies improves the teaching-learning process, and promotes the construction of significant learning in students. For the development of this Curricular Integration Work, the general objective was: "To promote the construction of significant learning in students, through the implementation of playful didactic strategies, in the teaching-learning process of the subject of Chemistry, in the first year of Baccalaureate, of the "Daniel Álvarez Burneo" Educative Unit, during the academic period 2022 - 2023 ". The research method used was inductive, since, thanks to direct observation, the problem could be identified, to later elaborate and develop an intervention proposal, which improves the problem circumstances. Regarding the approach, this is qualitative, the relevant characteristics of the teaching-learning process were determined. In addition, according to the nature of the information, it is of the participatory action research type; since, the study subjects were directly interacted to promote solutions to the identified problem. According to the temporality it is transversal, due to the short period during which the research was carried out. The results obtained through the research and evaluation instruments applied, demonstrated that the implementation of games such as: crossword puzzle, word search, bingo of the periodic table and quiz, are the activities that mostly allowed the significant improvement of the teaching and learning process of Chemistry, and therefore the construction of significant learning in students. It is concluded that the playful didactic strategies, implemented in the development of the teaching and learning process of Chemistry, effectively promote the active participation and at the same time, the construction of significant learning in students. Key words: teaching and learning process, games, active participation, academic curiosity.